PRIME LABELING OF SOME WEB GRAPHS WITHOUT CENTER - Scada, Jovanco Albertha; Susanti, Yeni (Diponegoro University, 2024)
The prime labeling of a graph \(G\) of order \(n\) is a bijection function from the set of vertices in \(G\) to the set of the first \(n\) positive integers, such that any two adjacent points in \(G\) have labels that are coprime to each other. In this paper we discuss the primality of the graph \(W_0(2,n)\) along with its combinations with similar graphs and various types of edges subdivisions in the graph \(W_0(2,n)\). Moreover, it is also presented the necessary and sufficient conditions for the graph to be prime.